Drilling production management system - Устенко, А. О. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Management system of drilling production is researched. In general. management system represents the concept of interconnected and interdependent parts – components: scientific knowledge and practical skills to manage different objects (a person, a process, an organization) to ensure their competitiveness in the market conditions and the overall satisfaction with optimal usage of resources. The necessity of the creation of the theoretical model of wells construction process is grounded and the model itself is developed. Theoretical model with factors’ classifiers is seen not only as a managed system, but as an object for the managing system, which implements general management functions. The classification of factors with the determination of parameters and the classification of functions and tasks of the researched process is worked out. In this context, the boundaries of the differentiation of such notions as a "specific function", "functional complex of tasks", "task" are deliberately limited. A specific management function is defined as a set of all management functions of one of the stages of business activity. A functional complex of tasks is defined as a set of tasks which implement one of the specific management functions (e.g., planning one of the stages of business activity, accounting for one stage, etc.). A task of management is determined as the implementation of one of the specific functions concerning one of the factors (components), such as labor and wages planning, labor scheduling, etc.). The wells construction process is considered as a unified labor process and value creation process, as the unity of managed and managing subsystems.